Pengelolaan Objek Wisata Bukit Suligi Aliantan Kabupaten Rokan Hulu - Nurdesri Juni Amelia; Khairul Amri (LPPM Politeknik Pratama, 2024)
The phenomenon found in the Suligi Hill tourist attraction is a phenomenon in the management of the Suligi Hill tourist attraction in Aliantan, namely the existence of budget limitations resulting from the absence of financial assistance obtained from the government, both from the village government and regional government, which causes the management to be hampered in developing the Suligi Hill tourist attraction. . Apart from that, the result of limited funds is that the available facilities are inadequate. The research method used in this research uses descriptive qualitative research methods and uses primary data sources and secondary data. The data collection techniques that researchers use are interviews, observation and documentation. There were 10 informants in this study. The results of this research are that the management of the Suligi Hill tourist attraction in Aliantan, Rokan Hulu Regency, in implementing four management indicators for the management of tourist attractions, can be seen in the planning and organization which has gone quite well. Meanwhile, implementation and supervision have not been managed optimally. And readiness to implement the management concept of managing the Suligi Hill tourist attraction experiences several obstacles, namely the lack of budget for development from the government and human resources which sometimes have a lack of correlation, and limitations and lack of maintenance of supporting facilities at tourist destinations.